1993
DOI: 10.1113/jphysiol.1993.sp019510
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of respiratory activity of neonatal rat phrenic motoneurones by serotonin.

Abstract: SUMMARY1. The effects of serotonin on phrenic motoneurones were studied in an in vitro preparation of the isolated brainstem and spinal cord from neonatal rats.2. Serotonin (5-HT; ) 5-10 ltM) increased inspiratory-modulated phrenic nerve activity and produced a small amount of tonic activity during expiration. Inspiratory-modulated activity of the fourth cervical ventral root also increased, but was accompanied by robust tonic activity, which often obscured the rhythmic activity.3. Serotonin, in both normal an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
91
0
2

Year Published

1994
1994
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(102 citation statements)
references
References 40 publications
9
91
0
2
Order By: Relevance
“…Consistent with our findings, PKC modulates transient (Astman et al, 1998;Sitges et al, 1998;Schreibmayer, 1999) and persistent sodium currents (Astman et al, 1998;Franceschetti et al, 2000), and it has been proposed that these effects on sodium currents increase the neuronal excitability (Astman et al, 1998;Franceschetti et al, 2000). The activation of 5-HT 2A receptors has been associated with the induction of a tonic inward current (Lindsay and Feldman, 1993) that is Na Ï© dependent (Lee et al, 1999). In this study, we show that the inhibition of endogenous activation of 5-HT 2A receptors decreases the persistent and transient sodium current in the re- (COCKTAIL; top trace), the pacemaker neuron continues to generate intrinsically rhythmic activity (bottom trace).…”
Section: Role Of Endogenous Activation Of 5-ht 2a In the Maintenance supporting
confidence: 91%
See 1 more Smart Citation
“…Consistent with our findings, PKC modulates transient (Astman et al, 1998;Sitges et al, 1998;Schreibmayer, 1999) and persistent sodium currents (Astman et al, 1998;Franceschetti et al, 2000), and it has been proposed that these effects on sodium currents increase the neuronal excitability (Astman et al, 1998;Franceschetti et al, 2000). The activation of 5-HT 2A receptors has been associated with the induction of a tonic inward current (Lindsay and Feldman, 1993) that is Na Ï© dependent (Lee et al, 1999). In this study, we show that the inhibition of endogenous activation of 5-HT 2A receptors decreases the persistent and transient sodium current in the re- (COCKTAIL; top trace), the pacemaker neuron continues to generate intrinsically rhythmic activity (bottom trace).…”
Section: Role Of Endogenous Activation Of 5-ht 2a In the Maintenance supporting
confidence: 91%
“…Activation of 5-HT 2A receptors has a well documented excitatory effect not only in the respiratory network but also on different areas in the CNS (Araneda and Andrade, 1991;Lindsay and Feldman, 1993;Marek and Aghajanian, 1996). At the cellular level, ionophoresis of 5-HT 2A agonists (␣-Me-5-HT and DOI) depolarizes membrane potential and increases action potential frequency in respiratory neurons (Lalley et al, 1995;Onimaru et al, 1998), which results in an increase in respiratory rhythmic activity in the brainstem slice preparation (Al-Zubaidy et al, 1996;Onimaru et al, 1998).…”
Section: Role Of Endogenous Activation Of 5-ht 2a In the Maintenance mentioning
confidence: 99%
“…Neurons subjected to experimental measurements and data analysis satisfied criteria previously described (Liu et al, 1990;Lindsay and Feldman, 1993). Briefly, these neurons had resting membrane potentials of at least -60 mV and displayed rhythmic synaptic drive currents in synchrony with the inspiratory burst activity on the C, ventral root.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, localized injections of serotonin or serotonin agonists elicit both facilitatory and inhibitory influences on important classifications of medullary respiratory neurones (Sessle & Henry, 1985;Arita & Ochiishi, 1991). However, the net influence of increased supraspinal serotonin is an increase in respiratory frequency rather than nerve burst amplitude (Monteau, Morin, Hennequin & Hilaire, 1990;Morin, Monteau & Hilaire, 1991;Lindsay & Feldman, 1993). Millhorn et al (1980a) suggested that LTF operates via supraspinal mechanisms, a theory based on the observation that LTF occurs via changes in both phrenic burst amplitude and frequency.…”
Section: Possible Mechanismsmentioning
confidence: 99%